Which parameters drive approximation inaccuracies? - Sebastian Sienknecht (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2010)
This paper identifies parameters responsible for welfare reversals when the basic New Keynesian model is approximated. In our setting, a reversal occurs when the Ramsey policy under timeless perspective commitment ceases to be dominant against the Taylor rule after approximating the model. We find that the parameters involved are the degree of persistence in the autoregressive shock process and the labor elasticity of real output.
Keywords: E30; E52; E61; 330; optimal monetary policy; approximations; welfare analysis; timeless perspective; Geldpolitik; Zeit; Wohlfahrtseffekt; Neukeynesianische Makroökonomik; Theorie